2014
DOI: 10.1017/jie.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Why We Drop Out of School: Voices of San School Dropouts in Botswana

Abstract: Among San communities in Botswana, the rate of student disengagement from both primary and junior secondary school is an ongoing concern for educators. San learners leave school at all levels of primary and junior secondary education. Students who leave school have tended not to provide reasons as to why they are dropping out. This study investigated some of the reasons why San learners decided to drop out at primary and junior secondary school levels in the Central District in Botswana. In-depth interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…They are also required to work at home sometimes (Mahlomaholo, ; Smits & Huisman, ; Abhisek & Soumendu, ; Abuya et al., ; Banik & Neogi, ; Wudu, ; Sahin et al., ) (South Africa, Algeria, Egypt, Morocco, Syria, Tunisia, Yemen, Kenya, India, Ethiopia, Turkey). It is also common for students to be sent to do wage work to support the family financially (Farid‐ul‐Hasnain & Krantz, ; Flisher et al., ; Abuya et al., ; Mokibelo, ) (Pakistan, South Africa, Kenya, Botswana). Because guardians need to bring up their own children, they sometimes send non‐biological children to do wage labour to reduce the financial burden (No et al., ) (Cambodia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also required to work at home sometimes (Mahlomaholo, ; Smits & Huisman, ; Abhisek & Soumendu, ; Abuya et al., ; Banik & Neogi, ; Wudu, ; Sahin et al., ) (South Africa, Algeria, Egypt, Morocco, Syria, Tunisia, Yemen, Kenya, India, Ethiopia, Turkey). It is also common for students to be sent to do wage work to support the family financially (Farid‐ul‐Hasnain & Krantz, ; Flisher et al., ; Abuya et al., ; Mokibelo, ) (Pakistan, South Africa, Kenya, Botswana). Because guardians need to bring up their own children, they sometimes send non‐biological children to do wage labour to reduce the financial burden (No et al., ) (Cambodia).…”
Section: Discussionmentioning
confidence: 99%
“…The result is consistent with that of Korinek and Punpuing (2012) in Thailand, who confirmed that the odds of deserting school are relatively lower in areas with a large proportion of adults employed in managerial, professional and clerical positions, and a relatively smaller proportion engaged in agriculture. In other words, the engagement of the larger population in agriculture in rural regions provides no incentives for investment in children's education given the absence of future employment possibilities (Mahlomaholo, 2012;Edwards et al, 2014;Mokibelo, 2014;Tukundane et al, 2014) (South Africa, Cambodia, Botswana, Uganda). This boils down to the assertion by Lloyd et al (2009) and Chung and Mason (2012) in Pakistan and China, respectively, that development in a community is a statistically significant and important factor in reducing the odds of dropout.…”
Section: Schoolmentioning
confidence: 99%
“…At the primary level, Mokibelo (2014Mokibelo ( , 2016b) has written extensively on the challenges confronting English as a medium of instruction in rural public primary schools, while examining the language in education policy of Botswana. These include non-participation in lessons, poor understanding, incorrect use of pedagogy, relatively high school dropout rates, how English can demoralise the learners as they exhibit limited expressions in some basic language skills, learners do not achieve learning outcomes on completion of their studies at this level, and the imposition of English on learners can lead to agitation, perplexity and difficulty in reading.…”
Section: Botswanamentioning
confidence: 99%
“…The expectation is that learners have to obey the school rules and regulations. A good number of reasons that contributed to learners' disengagement from school have been advanced and these include: violence in hostels, corporal punishment, languages of instructions and the culture that is different from theirs (Mokibelo, 2014). The only jobs they would do was become herd-boys since the job does not require formal qualifications in Botswana at the moment.…”
Section: Learners' Rejection Of the Capitalist Education Systemmentioning
confidence: 99%